Analysis of Eevee Engine Rendering Engineering in Making 3D Animation Videos Mukomuko Hospital - Eka Sahputra; Muhardi Hari Sucahyo (Penerbit Jurnal Indonesia, 2022)
Blender is a free and open source 3D computer software, Blender is used to create animated films, visual effects, and video games. This software features 3D modeling, UV unwrapping, texturing, ringing and skinning, fluid and smoke simulation, particle simulation, animating, match moving, camera tracking, rendering, video editing, compositing and a built-in game engine. Where we can design and create 3D animated films not only as a medium of entertainment in cinema, but also can be used in various fields including visual socialization media, which can bring new colors in the delivery of information. The formulation of this research is to determine how long the render time is generated to perform the rendering process using the Eevee rendering engine in Blender Software with a video duration of 54 seconds and a resolution of 320, 720, 1080 pixels on the 3D animation video of Mukomuko Hospital and the quality of the graphics/visuals produced by Eevee rendering engine. The animation video used is the 3D animation “Mukomuko Hospital”. The process of making animation using Blender 3D application and Adobe Premiere CC animation video design. The software used is Blender 2.82. The duration of the video analyzed using Eevee Engine Render is 54 seconds. The image resolution analyzed using the Eevee Engine is 320, 720 and 1080 pixels. The conclusion of this research is in the pre, production and post production process of 3D animation video at RSUD Mukomuko in accordance with the planning made previously. The rendering time generated to perform the rendering process using the Eevee rendering engine in Blender Software with a video duration of 54 seconds and a resolution of 320, 720, 1080 pixels, obtained various results with their respective advantages and disadvantages.